Hubungan Pengetahuan Tata Rias dengan Penampilan Profesional Guru di SMKN Kota Padang - Putri Afsyari Chan; Febri Silvia (STIKes Ibnu Sina Ajibarang, 2025)
Professional appearance is a very crucial aspect for an educator, especially in the context of vocational education such as State Vocational High Schools (SMKN), where educators act as role models for students. One element that can support professional appearance is knowledge in the field of make-up. The use of appropriate make-up not only reflects the level of professionalism, but can also increase self-confidence and reflect a good work ethic. This study aims to analyze the relationship between make-up knowledge and the professional appearance of educators at SMKN Padang City. The research method used is quantitative with a correlational approach. The sample in this study amounted to 53 female teachers from SMKN 06 and SMKN 07 Padang City who were selected using the proportional stratified random sampling technique. Data collection was carried out through observation, interviews, and questionnaires, then analyzed using a correlation test. The results of the study showed that there was a significant correlation between the level of make-up knowledge and the professional appearance of teachers. Educators who have good insight in the field of make-up generally show a more well-groomed appearance, are full of confidence, and reflect professional standards in the educational environment. Based on these findings, it can be concluded that increasing knowledge about make-up makes a positive contribution to the formation of a professional image of teachers in the SMKN environment.